Wireless Ammonia Sensor System for Distributed Wireless Monitoring Platform using Heltec Wifi LoRa 32 (V2) - Mohd Redzuan, Ahmad Afif Aiman; Saparudin, Faiz Asraf; Mohd Shah, Nor Shahida; Noor Azeb, Muhammad Mirza Amsyar; Shamsuddin, Muhamad Khairi Azizi (Progress in Engineering Application and Technology, 2021)
The Distributed Wireless Monitoring Platform (DWMP) is a system available for water quality monitoring (WQM) at several locations within a large range using wireless technology. The goal of this project is to research and design a wireless sensor system that use low-powered devices and uses a wireless connection for the wireless ammonia sensor system which will deployed in water from river in forest area. Heltec Wifi Lora 32 (V2) is used as the main device for the wireless ammonia sensor system that will then functions to detect the analog value of the sensor and send the data to gateway part for monitoring operation. Experiments have been conducted to evaluate the performance of the sensor system. RSSI or signal strength and the power used by the sensor node are observed for this project are accessed on the gateway or receiver part. Power consumed by the sensor device is determined during the device is in running mode and during deep sleep. The parameters such as height and distance between sensor node and gateway is varies and can achieved up to 500 m if the sensor node is on the ground level and about 800 m in the height is increased to 2.5 m from the ground. To conclude, results from the experiments shows that the design implementations using LoRa technology from Heltec Wifi LoRa 32 (V2) are capable to be used for real time monitoring operations at a larger radius which is suitable for DWMP system.